Implementation of Academic Supervision With Class Visit Technique By The Principal In An Effort to Improve Teacher Performance at SMPN 5 Pamekasan - Masti Yanto; Nailatur Rizqiyah; Waqiatul Masruroh; Moh Elman (Lembaga Einstein College (LEC), 2025)
The aim of this research is to get to know the application of academic supervision using class visit techniques carried out by the school principal in an effort to improve teacher performance at SMPN 5 Pamekasan. This paper applies a qualitative method which more precisely uses a descriptive type. The subject of this research is the principal of SMPN 5 Pamekasan. Meanwhile, the results of this research can be concluded that the implementation of academic supervision using class visit techniques by the school principal goes through several stages, including: First, the planning stage. The steps taken at the planning stage include: preparing performance plans through performance management at PMM, preparing tools for educators and a way to collect and process data, determining class visit schedules, and holding discussions with teachers regarding the performance plans that have been made. they arrange. Second, the implementation stage. Third, evaluation, reflection and follow-up stage. In the implementation of supervision there are supporting and inhibiting factors. The supporting factor is the existence of the PMM application which makes it easier for school principals to carry out supervision, while the inhibiting factor is the limited time to carry out supervision activities. Considering that the principal has so many duties, supervision activities cannot be carried out optimally.